2021
DOI: 10.5306/wjco.v12.i5.382
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal metastasis from breast cancer: Presentation, treatment and survival from a systematic literature review

Abstract: BACKGROUND Intestinal metastases from breast cancer (BC) arerare; available data depend mainly on case reports and case series. AIM To conduct a review of the literature regarding presentation, diagnosis, treatment and survival of patients with intestinal metastasis from BC. METHODS We identified all articles that described patients with intestinal metastasis (from duodenum to anum) from BC using MEDLINE (1975 to 2020) and EMBASE (1975 to 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…Notably, despite being accounted for only less than 15% of all histologic breast cancer subtypes, invasive lobular carcinoma (ILC) is much more frequently encountered in metastasizing to the GI tract, rather than the more common invasive ductal carcinoma (IDC) [ 2 ]. In a study of 96 breast cancer patients with GI metastases, there were 56 patients who had lobular carcinoma, while only 17 patients had ductal carcinoma [ 4 ]. Another study conducted by McLemore et al also revealed that ILC contributed to 64% of all GI metastases [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, despite being accounted for only less than 15% of all histologic breast cancer subtypes, invasive lobular carcinoma (ILC) is much more frequently encountered in metastasizing to the GI tract, rather than the more common invasive ductal carcinoma (IDC) [ 2 ]. In a study of 96 breast cancer patients with GI metastases, there were 56 patients who had lobular carcinoma, while only 17 patients had ductal carcinoma [ 4 ]. Another study conducted by McLemore et al also revealed that ILC contributed to 64% of all GI metastases [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the prognosis of the gastrointestinal metastatic breast cancer group is still poor. The average survival time from detecting gastrointestinal metastases is 1 years [ 4 ]. As in our case, the patient presented with rectal and lung metastases simultaneously; although bleeding and difficult defecation were partially improved, the patient also progressed rapidly after six cycles of chemotherapy gemcitabine - carboplatin Due to limited data, surgery such as low anterior resection and abdominoperineal resection has not been shown to improve survival in this situation.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the literature, the GI tract was rarely a preferred metastatic site for breast cancer in particular [ 10 ]. Thus Apodaca-Rueda M et al had reported a case of metastasis to the pancreatic level [ 11 ], Nour A et al, described a metastasis to both the colonic and gastric level initially taken as primary [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors report digestive metastases of a breast primary discovered in a context of complication or emergencies like Théraux J et al who had described a colonic occlusion on a colonic tumor of breast origin [ 13 ] and Nehmeh WA et al had reported a secondary localization following a gastric perforation [ 14 ], while hematemesis revealed the diagnosis in our case. This sporadic case is described among less than 50 cases reported through the literature [ 14 ] and the treatment of its rare forms of GI metastases of breast origin is based on palliative chemotherapy [ 10 ] with a poor prognosis [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common gastrointestinal metastasis site is stomach with about 60% of cases, followed by esophagus, colon, small intestine and rectum [ 6 ]. In one literature review, the median survival rate was 12 months from the diagnosis of intestinal metastasis of breast cancer [ 7 ]. The GI tract metastasis is usually detected at around 50–78 months after the detection of primary breast cancer [ 4 ].…”
Section: Introductionmentioning
confidence: 99%